2008
DOI: 10.1074/jbc.m709966200
|View full text |Cite
|
Sign up to set email alerts
|

MMP-12 Catalytic Domain Recognizes Triple Helical Peptide Models of Collagen V with Exosites and High Activity

Abstract: Collagens are principal constituents of connective tissues. They are hydrolyzed during development, wound repair, and remodeling of the extracellular matrix. Dysregulated collagenolysis is active in inflammatory diseases such as atherosclerosis, cancer, rheumatoid arthritis, periodontitis, and liver and kidney pathologies. Matrix metalloproteinases (MMPs) 3 play key roles in these processes (1-3). Mutagenesis has established the importance of the V-B loop (joining ␤-strand V and helix B) in collagenolysis by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 91 publications
1
36
0
Order By: Relevance
“…The hydrolysis of fTHP-15 by each of these MMPs with the exception of MMP-12 has been reported previously (16 -18, 22, 40) and occurs at the Gly2Leu bond. MMP-12 hydrolysis of fTHP-15 was considerably slower than for other MMPs (Table 2) and much slower than for MMP-12 hydrolysis of an fTHP derived from type V collagen (58). The MMP-12 used herein lacks a C-terminal hemopexin-like domain, which enhances MMP-12 catalytic activity for the type V collagen fTHP (58).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The hydrolysis of fTHP-15 by each of these MMPs with the exception of MMP-12 has been reported previously (16 -18, 22, 40) and occurs at the Gly2Leu bond. MMP-12 hydrolysis of fTHP-15 was considerably slower than for other MMPs (Table 2) and much slower than for MMP-12 hydrolysis of an fTHP derived from type V collagen (58). The MMP-12 used herein lacks a C-terminal hemopexin-like domain, which enhances MMP-12 catalytic activity for the type V collagen fTHP (58).…”
Section: Resultsmentioning
confidence: 97%
“…The MMP-12 used herein lacks a C-terminal hemopexin-like domain, which enhances MMP-12 catalytic activity for the type V collagen fTHP (58). Nonetheless, the MMP-12 catalytic domain possesses collagenolytic activity (57,58) and is the physiologically relevant form of MMP-12 (59), and fTHP-15 serves as a well established point of reference for all of the MMPs.…”
Section: Resultsmentioning
confidence: 99%
“…Second, a SDP subset we identified here in the SV-hB loop (Fig. 4) colocalizes with the region that is required for the collagenolytic activity of several MMPs (35,38,39). This colocalization raises questions as to whether these particular SDPs distinguish the collagenolytic vs. noncollagenolytic MMPs (see below).…”
Section: Discussionmentioning
confidence: 97%
“…This observation suggested that particular positions contribute to substrate recognition in varying degrees. This idea was tested by calculating the sequence-activity correlation coefficient (SACC), which determines the impact of sequence variability at each position on substrate cleavage (35). An SACC score of 1 indicates the total dominance of substrate recognition by that position, whereas a 0 score indicates a lack of any effect.…”
Section: Resultsmentioning
confidence: 99%
“…We performed molecular modeling of the substrates followed by docking analyses of the catalytic domain of MT1-MMP with the two substrates (details in Materials and Methods). Our docking results were compared with available NMR structures of structurally homologous MMP-collagen systems (24,28), showing that the collagen-like substrates exist in either stretched or bended configurations (SI Appendix, Fig. S1).…”
Section: Resultsmentioning
confidence: 99%